Materializing interactions with paper prototyping: A case study of designing social, collaborative systems with older adults. (September 2019) - Hanrahan, Benjamin V.; Yuan, Chien Wen; Rosson, Mary Beth; Beck, Jordan; Carroll, John M.
Abstract : Paper prototypes have been successful for gathering concrete, grounded user feedback. Most of these prototypes are used to elicit feedback during bounded design sessions. However, for systems that support new social practices these bounded sessions do not fully materialize the interactions the prototype supports. This paper presents a case study of a six-month paper prototype deployment that materialized collaborative interactions in care retirement community. Throughout this deployment the prototype was situated within the lives of participants, where they shaped the interactions and usage of the prototype over time. As these interactions materialized, the evoked community practice was unlike what participants envisioned during our first, more traditional paper prototyping and design sessions. This article shows how our interactive, paper prototype provided critical guidance in how realistic our imagined practice would be. Highlights: Deploying a paper prototype for months, not hours, at a time can reveal more detail. Creative use of paper prototypes can support collaborative and social practices. Temporal and physical space to evolve prototypes grants more accessible participation.